Early‐onset versus late‐onset Crohn's disease: An Italian cohort study. Issue 1 (1st February 2020) - Cantoro, Laura; Lenti, Marco Vincenzo; Monterubbianesi, Rita; Cicala, Michele; Giannarelli, Diana; Papi, Claudio; Kohn, Anna; Di Sabatino, Antonio
Abstract : Background: Disease heterogeneity, according to the age at onset, has been reported in Crohn's disease (CD). Objective: This study aimed to compare natural history in CD patients diagnosed ≤17 (early onset (EO)) versus ≥60 (late onset (LO)) years old. Methods: EO CD and LO CD patients referred to two Italian inflammatory bowel disease (IBD) centres were included. Relevant data comprised sex, current smoking, disease location and behaviour, IBD family history, extra‐intestinal manifestations and use of medical/surgical therapy during the follow‐up period. Results: Among 2321 CD patients, 160 met the inclusion criteria: 92 in the EO and 68 in the LO group (mean follow‐up 11.7 ± 7.7 years). Family history of IBD was more frequent in EO compared to LO CD (26% vs. 4%; p < 0.0001). Ileocolonic, upper gastrointestinal and perianal involvement occurred more frequently in EO compared to LO CD (56% vs. 21%, p < 0.0001; 17% vs. 3%, p < 0.01; and 38% vs. 19%, p < 0.01, respectively). Progression to complicated disease occurred more frequently in EO CD (40% vs. 10% p < 0.005), with an increased use of corticosteroids and anti‐tumour necrosis factor alpha agents within 10 years since diagnosis (81% vs. 58%, p = 0.004, and 36% vs. 16%, p = 0.01, respectively), while the cumulative probability of surgery did not differ between the two groups. Conclusions: Patients with EO CD are more likely to develop a more aggressive disease with perianal involvement and a greater use of drug treatment compared to those with LO CD, without carrying an increased need for surgery.